Seroprevalence Of Toxoplasma Antibodies In Cats In Chennai - Bharathi, M.Vijaya; Sreekumar, C.; Thanhadurai , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Sera samples collected from 100 cats in and around Chennai, India were analysed for antibodies to Toxoplasma gondii by modified direct agglutination test (MDAT). 39 per cent seroprevalence was recorded in cats, which had, titre values of 1:64 and above. Clinical feline toxoplasmosis was analyzed. Statistically the sex-wise and age-wise seroprevalence were found to be significant.